ANALYSIS AND EVALUATION FUSELAGE SECTION’S CRASHWORTHINESS OF TYPICAL CIVIL AIRPLANE BASED ON PASSENGER RESPONSE - ZHU XianFei; FENG YunWen; XUE XiaoFeng; ZHU ZhengZheng (Jixie qiangdu)
The ultimate goal of aircraft crashworthiness design is to protecting safety for occupants. In order to more accurately simulate the dynamic response and injury of the occupants during crash event,a crash simulation model of the fuselage section which including dummy and seat restraint system was developed using LS-Dyna,and the dynamic response of the structure and occupants is analyzed in detail when the vertical impact velocity is 9. 14 m/s,the analysis includes the energy absorption characteristics and failure mode of the fuselage structure,the mooring condition of the cabin facilities,the movement and injury of the occupants,etc.,and the validity of the crash simulation model is verified by comparison simulation results with the test data.Finally,the research on the evaluation method of civil aircraft crashworthiness was carried out. Through understanding and identification of relevant airworthiness clauses,advisory circular and standards,the comprehensively evaluation method to evaluating the crashworthiness of civil aircraft was proposed based on the survival space,the strength of mooring,the injury of occupants,the evacuation channel and the post-crash environment. The crashworthiness analysis of the fuselage section shows that the injury modes of occupant in the vertical crash environment are mainly lumbar and tibia injuries,the occupant’s maximum compression lumbar load is 6. 78 k N,and the maximum axial tibia load is 7. 46 k N during the crash process. The crashworthiness of the constructed civil aircraft is systematically evaluated by the comprehensive crashworthiness evaluation method proposed in this paper,it shows that the crashworthiness of this civil aircraft is good,except for the occupant’s lumbar load slightly exceeding the airworthiness limit and requiring corresponding design improvements,the other evaluation indexes are all in accordance with the requirements.